Synthesis and antioxidant properties of some new 5-phenethyl-3-thio-1, 2, 4-triazoles - Ihnatova, T.; Kaplaushenko, A.; Frolova, Yu.; Pryhlo, E.; Каплаушенко, Андрій Григорович; Фролова, Юлія Сергіївна; Пругло, Євген Сергійович (My University, 2021)
Novel derivatives of 4-R-5-phenethyl-4H-1,2,4-triazole-3-thiols were synthesized. The proposed approaches and developed synthetic protocols provided the possibility to design 4-R-5-phenethyl-4H-1,2,4-triazole-3-thiols and their derivatives have been shown. The antioxidant activity of the synthesized compounds was evaluated in vitro by the method of the non-enzymatic initiation of BOD with salts of iron (II). When compared with existing antioxidants, some of our compounds were found to be more potent.
Keywords: 1,2,4-triazole; antioxidant activity; synthesis